2019
DOI: 10.1016/j.cyto.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in RORA are associated with asthma and allergy markers in an admixed population

Abstract: Asthma and allergy affect hundreds of millions of people from childhood to old age. In most of them, the inflammatory process of respiratory allergies involves the participation of type 2 cytokines, derived from T helper-2 (Th2)-cell, and Group 2 Innate Lymphoid (ILC2) Cells. An efficient memory Th2 cell response is dependent on IL-13 produced by ILC2s, causing allergic lung inflammation and elevated serum levels of immunoglobulin E. ILC2 cells are derived from common lymphoid progenitors and their growing dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Four of the SNPs correlated with levels of tIgE in asthmatics (with the asthma risk allele associated with increased levels of tIgE, Supplementary Table 19), suggesting that these asthma risk alleles may lead to an increased Th2 immune response. This includes SNP rs1420101 in the IL1R1 locus (a gene that is known to correlate with eosinophilia 35 ), SNP rs10519067 intronic to the RORA gene (encoding a transcription factor that regulates the growth of group 2 innate lymphoids, a key cell type in the memory Th2 cell response 36 ), and SNPs rs907092 and rs2952156 in the chr17q12–21 locus. These results are consistent with previous studies that have shown both shared and unique associations between these phenotypes 3741 .…”
Section: Resultsmentioning
confidence: 99%
“…Four of the SNPs correlated with levels of tIgE in asthmatics (with the asthma risk allele associated with increased levels of tIgE, Supplementary Table 19), suggesting that these asthma risk alleles may lead to an increased Th2 immune response. This includes SNP rs1420101 in the IL1R1 locus (a gene that is known to correlate with eosinophilia 35 ), SNP rs10519067 intronic to the RORA gene (encoding a transcription factor that regulates the growth of group 2 innate lymphoids, a key cell type in the memory Th2 cell response 36 ), and SNPs rs907092 and rs2952156 in the chr17q12–21 locus. These results are consistent with previous studies that have shown both shared and unique associations between these phenotypes 3741 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, genetic studies of asthma show that certain polymorphisms promote ILC2 development. Specifically, polymorphisms in the 15q22.2 locus are associated with asthma risk, particularly therapy-resistant asthma, and this locus contains the RORA gene that codes for the RAR-related orphan receptor-a (ROR-a) transcription factor that controls ILC2 development (Lima et al, 2019;Persson et al, 2015). Some cautionary notes about all these studies describing the presence or activation of ILC2s in asthmatics are that ILC2s are a scarce population of lymphocytes that can be contaminated by CD4 adaptive lymphocytes that downregulate TCR expression (Hinks et al, 2017) and that ILC2s are quite flexible cells that can differentiate into IFN-g-producing ILC1s in periods of exacerbation (Ohne et al, 2016;Silver et al, 2016).…”
Section: Reviewmentioning
confidence: 99%
“…The Th2 response is derived from interleukin-13 produced by ilc2, while ilc2 cells are derived from normal lymphoid progenitor cells, and their growth depends on RORA. 20 AMI is an inflammatory disease. Inflammation increases the incidence of complications of AMI and increases the mortality rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…growth depends on RORA. 20 AMI is an inflammatory disease. Inflammation increases the incidence of complications of AMI and increases the mortality rate of patients.…”
Section: Discussionmentioning
confidence: 99%